2022
DOI: 10.1186/s13052-022-01252-3
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary care for patients with epidermolysis bullosa from birth to adolescence: experience of one Italian reference center

Abstract: Background Epidermolysis bullosa (EB) is a disabling and chronic genodermatosis characterized by mucocutaneous fragility with blister formation after minimal trauma. Severity ranges between very mild forms to extremely severe or lethal subtypes. Depending on disease subtypes, blisters may be localized also in larynx, bladder, esophagus, and most frequent disease complications are malnutrition, chronic anemia, osteoporosis, limb contracture and early development of squamous cell carcinomas. EB i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The third theme identified in the present study addressed the complexity and challenges of a multi-disciplinary setting of care, in which effective communication was believed to ensure integration with continuity of care. The multi-disciplinary approach in dermatology has been reported in a previous study of pediatric patients with epidermolysis bullosa, resulting in improved quality of life-related outcomes and greater adherence to treatment [ 10 ]. The multi-disciplinary approach requires a case manager, who may be one of the HCPs described in the present study, including the integrative physician with training and experience in supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…The third theme identified in the present study addressed the complexity and challenges of a multi-disciplinary setting of care, in which effective communication was believed to ensure integration with continuity of care. The multi-disciplinary approach in dermatology has been reported in a previous study of pediatric patients with epidermolysis bullosa, resulting in improved quality of life-related outcomes and greater adherence to treatment [ 10 ]. The multi-disciplinary approach requires a case manager, who may be one of the HCPs described in the present study, including the integrative physician with training and experience in supportive care.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the level of tissue separation and cleavage planes within the skin basement membrane, four major types of EB are currently described: EB simplex (EBS), junctional EB (JEB), dystrophic EB (DEB), and Kindler EB (KEB). To date, no specific curative treatment exists for EB [ 26 ]. The prevention of new blisters development and accurate wound care represent the optimal therapeutic approach.…”
Section: Staphylococcal Infections In the Neonate With Epidermolysis ...mentioning
confidence: 99%
“…Epidermolysis bullosa is a chronic genodermatosis with different phenotypes and severity. Retrosi et al [31] reported on treatment in 3 groups of patients: < 5 years, > 5-12 years and > 12-18 years. In the first group, the family should change lifestyle and burden of caring on quality of life is high.…”
Section: -Epidermolysis Bullosamentioning
confidence: 99%